Development Of Website-Based Management Information Systems for Building Construction - Ramadhan Abdurrahim, Muhammad (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2022)
Project managers are generally constrained by limited time and location to monitor the implementation of daily construction tasks. This problem makes monitoring and coordination run slowly. By utilizing internet technology, the author aims to develop an online management information system that computers or smartphones can access for stakeholders. This research aims to ease tasks such as progress reports and field monitoring with a database that can store soft copies of project data on one server. The analysis follows the waterfall method, requirements, design, coding, and testing in the local server, then uploads the .php index to the database server. This website application helps managers, owners, and other employees by facilitating the process of monitoring, reporting, and discussing even remotely. Using programs such as HTML, PHP, and MySQL, the author developed a website that speeds up the managerial process and creates a database server for storing digital documents. Users of this application were assessed a scale of 1 to 5: Interface design: 4.25, User-friendliness: 4.5, Facilities: 4, Access speed: 3.25, so it has an overall score of 4.25 out of 5.